Photoelectric degradation zirconium-based MOF (Metal Organic Framework) composite film as well as preparation method and application thereof

By combining zirconium-based MOF with zinc oxide particles, forming a composite photoelectric catalyst and uploading it to the surface of the metal substrate, the problem of difficult catalyst recovery and fast carrier recombination in traditional photocatalytic technology is solved, and efficient degradation of organic pollutants and good repeatability is achieved.

CN119793538APending Publication Date: 2025-04-11GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510008236.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional photocatalytic technology has the problem of difficulty in recycling catalysts and fast carrier recombination, resulting in low photocatalytic activity.

Method used

By combining the zirconium-based metal organic frame (MOF) with zinc oxide particles, a composite photoelectric catalyst is formed and uploaded to the surface of the metal substrate to form a photoelectric anode composite film. The film was prepared by hydrothermal method and chemical precipitation method to prepare zinc oxide particles, combined with alcohol solution and dilute alcohol solution for ultrasonic dispersion, and finally uploaded to the surface of the metal substrate by drop coating method and calcined.

Benefits of technology

The stability and reuse ability of photoelectric catalysts are improved, and the degradation efficiency of organic pollutants is significantly improved. Especially under photoelectric conditions, the removal effect of tetrabromophenol is significantly improved and has good repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793538A_ABST
    Figure CN119793538A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoelectrocatalytic degradation, in particular to a zirconium-based MOF (Metal Organic Framework) composite membrane capable of performing photoelectrocatalytic degradation on organic pollutants as well as a preparation method and application of the zirconium-based MOF composite membrane. According to the invention, porous foam titanium is taken as a substrate to load a composite photoelectric catalytic layer, and the composite photoelectric catalytic layer comprises a metal organic framework (MOFs) taking zirconium as a metal center and zinc oxide (ZnO) nanoparticles prepared and synthesized by a chemical precipitation method. By means of high mechanical strength and good conductivity of metal titanium, the recycling life of an electrode is prolonged, the problem of poor conductivity of an MOFs material is solved, meanwhile, continuous operation of the MOFs photoelectric anode composite film in a flow-type reactor is achieved by means of a height-adjustable topological structure and a large specific surface area of the MOFs material and the excellent photocatalytic characteristic of ZnO, and the application range of the MOFs photoelectric anode composite film is widened. The contact between pollutants and a composite membrane interface is increased to improve the catalytic efficiency. The zirconium-based MOF can be used for realizing the photoelectrocatalytic degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental materials and water treatment technology, and in particular to the preparation and application of a zirconium-based MOF composite membrane capable of photoelectrocatalytically degrading organic pollutants in water. Background Art

[0002] Catalysis can directly utilize solar energy and is a potential technology for green energy production and environmental remediation. From a mechanistic point of view, the photocatalytic process involves the photocatalyst material absorbing light and then reacting with it. - From the valence band (VB) to the conduction band (CB), thus forming e - -h + Yes. Subsequently, these charge carriers can participate in redox reactions with adsorbed organic molecules or water to produce reactive oxygen species such as hydroxyl radicals and superoxide radicals, which are mainly responsible for degrading organic matter into less harmful inorganic ions. However, traditional photocatalysis has the problems of difficult catalyst recovery and rapid carrier recombination during the reaction, resulting in low photocatalytic activity. To overcome the above limitations, we loaded the photocatalyst on a membrane material to solve the problem of difficult catalyst recovery, and introduced electrocatalytic technology to alleviate the rapid recombination of carriers.

[0003] Photoelectrocatalysis can achieve efficient separation of charge carriers to a certain extent, and this technology has been successfully applied to many fields such as water separation, inorganic ion reduction and catalytic degradation of organic pollutants. Some studies have combined ZnO with Co and Ni to form core-shell layered metal oxides, and used the photogenerated electron-hole separation in the ZnO core and the electrocatalytic activity of the layered oxide shell to improve the photocurrent density and stability, but this study did not improve the photoactivity by optimizing the material. In addition to the coupling of optoelectronic technology, it has been found that MOFs, a type of material with ultra-high specific surface area, high hydrophilicity and abundant active sites, provide more active sites and additional migration pathways for the migration of photoinduced electrons in photocatalysis due to the adjustability of their ligands, large specific surface area and high porosity, thereby fundamentally promoting the separation of carriers. Summary of the invention

[0004] The present invention aims to provide an anode composite membrane capable of photoelectrocatalytic degradation and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a zirconium-based MOF composite film for photoelectric degradation, characterized in that it comprises a metal substrate and a composite photoelectric catalyst stacked in sequence, wherein the composite photoelectric catalyst is flaky zinc oxide particles and a zirconium-based metal organic framework with an octahedral cubic morphology.

[0007] Preferably, the total loading amount of the composite photoelectric catalyst on the metal substrate is 2.672-4 mg / cm 2 .

[0008] The present invention also provides a method for preparing the above-mentioned zirconium-based MOF composite mold, comprising:

[0009] The original metal substrate is sequentially placed in a ketone solvent, an alcohol solvent, and a mixed acid solution for ultrasonic immersion to perform degreasing and etching treatments, and then dried to obtain a pretreated metal substrate film;

[0010] The metal salt and the ligand powder are uniformly mixed with the mixed solution to obtain a precursor solution of the metal organic framework;

[0011] The precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the metal organic framework was obtained after cooling, washing and drying by a hydrothermal method;

[0012] A soluble zinc source is mixed with an alkaline solution, and zinc oxide particles with light-responsive characteristics are obtained by stirring, washing, and drying through a chemical precipitation method;

[0013] Dispersing zinc oxide particles and metal organic framework powder in a certain ratio in an alcohol solution and a dilute alcohol solution in turn by ultrasonication to obtain a composite photoelectrocatalyst dispersion;

[0014] The dispersion is slowly dripped onto the pretreated surface of the metal substrate, dried at room temperature and then calcined to obtain the photoanode composite film.

[0015] Preferably, the metal substrate is one of titanium sheet, nickel foam, and porous titanium foam; the ketone solvent is acetone or butanone; the alcohol solvent is one of methanol and ethanol; the ultrasonic time is 5 to 30 minutes; the mixed acid solution includes hydrofluoric acid (HF), nitric acid (HNO3) and water, and the volume ratio thereof is 1:(1 to 5):(19 to 23); the immersion time is 30 to 90 seconds; the drying temperature and time are 60 to 90°C and 8 to 16 hours, respectively.

[0016] Preferably, the metal salt is zirconium tetrachloride (ZrCl4) or zirconium oxychloride octahydrate (ZrOCl2·8H2O), and the metal ligand is one of terephthalic acid (H2BDC), trimesic acid (H3BTC), and porphyrin molecule, and the molar ratio is (1-4):1; the mixed solution includes formic acid (HCOOH) and N,N-dimethylformamide (DMF), and the volume ratio is (1-4):1.

[0017] Preferably, the stirring time of the precursor solution is 15 to 60 minutes; the hydrothermal temperature and time of the precursor solution are 100 to 140°C and 12 to 36 hours respectively; the cooling time after hydrothermal treatment is 6 to 12 hours; the washing solution is acetone, methanol and pure water, and their volumes are 30 to 90 mL, 60 to 120 mL and 100 to 180 mL respectively; the drying temperature and time are 60 to 90°C and 8 to 16 hours respectively.

[0018] Preferably, the soluble zinc source is zinc nitrate hexahydrate (Zn(NO3)2·6H2O) or zinc acetate dihydrate (Zn(CH3COO)2)·2H2O), and its concentration is 0.1-0.5 mol / L; the alkaline solution is sodium hydroxide (NaOH) or potassium hydroxide (KOH), and its concentration is 1-5 mol / L; the volume ratio of the reaction solution is 1:(1-3); the stirring time is 15-45 min; the washing solution is 100-200 mL of pure water; the drying temperature and time are 60-90°C and 8-16 h, respectively.

[0019] Preferably, the mass ratio of the zinc oxide particles to the metal organic framework is (1-3):1; the alcohol solution is 100-500 μL ethanol; the dilute alcohol solution includes ethanol and pure water in a volume ratio of (1-5):1; and the ultrasonic time is 15-45 min.

[0020] Preferably, the room temperature drying time of the metal substrate after the dispersion is dripped is 30 to 90 minutes; the calcination temperature and time are 300 to 450° C. and 60 to 120 minutes, respectively.

[0021] The present invention also provides an application of a zirconium-based MOF composite membrane in a circulating filtration system for removing organic pollutants in wastewater, wherein the organic pollutant is tetrabromophenol; and the pollutant-containing influent includes a sodium sulfate electrolyte with a concentration of 50 mM.

[0022] The present invention provides a method for preparing a photoelectric anode composite film that can perform photoelectrocatalytic degradation of organic pollutants in wastewater, comprising the following steps: placing an original metal substrate in a ketone solvent, an alcohol solvent and a mixed acid solution in turn for degreasing and etching treatment to obtain a desired metal substrate; fully stirring a metal salt and a ligand powder in a mixed solution of an acid and an organic solvent in proportion to obtain a metal organic framework precursor solution; transferring the uniformly mixed precursor solution to a stainless steel reactor lined with polytetrafluoroethylene, preparing by a hydrothermal method, cooling and washing to obtain a metal organic framework; mixing a soluble zinc source with an alkaline solution, and preparing zinc oxide particles by a chemical precipitation method; dispersing the metal organic framework and zinc oxide particles in an alcohol solution at a certain mass ratio to obtain a composite photoelectrocatalyst dispersion; applying the dispersion droplets on the pretreated metal substrate, drying at room temperature and calcining to obtain the photoelectric anode composite film. The present invention first prepares the metal organic framework and zinc oxide particles separately, and then applies the dispersion droplets of the two powders on the surface of the metal substrate to form a film at room temperature and calcining, which is simple and efficient to operate. In the embodiment, in the circulating filtration operation mode, tetrabromophenol was degraded and compared with the original metal substrate and the metal substrate loaded with the composite photoelectric catalyst under the conditions of no light and no electricity, pure electricity and photoelectricity, and repeated experiments were performed to study the degradation and mineralization ability and repeatability of the photoelectric anode composite membrane provided by the present invention on organic pollutants. The results show that the photoelectric anode composite membrane loaded with the composite photoelectric catalyst on the metal substrate has a significantly improved removal effect on tetrabromophenol under photoelectric catalytic conditions and has good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a scanning electron microscope image of MOF-808 in Example 1;

[0024] Figure 2 is a scanning electron microscope image of ZnO in Example 1;

[0025] Figure 3 This is a scanning electron microscope image of the photoanode composite film (Ti foam / ZnO / MOF-808) in Example 1;

[0026] Figure 4 The linear voltammetry (LSV) curves of Ti foam / ZnO / MOF-808 and the original metal substrate (Ti foam) in Example 1 and Comparative Example 1 are shown;

[0027] Figure 5 This is a comparison chart of the degradation of 10 mg / L tetrabromophenol by the photoanode composite film (Ti foam / ZnO / MOF-808) in Example 1 under no light and no electricity, pure electricity and photoelectric conditions;

[0028] Figure 6This is a comparison chart of the degradation of 10 mg / L tetrabromophenol by the original metal substrate film (Ti foam) in Comparative Example 1 under no light and no electricity, pure electricity and photoelectric conditions;

[0029] Figure 7 This is a comparison chart of the degradation of 10 mg / L tetrabromophenol by the photoanode composite film (Ti foam / ZnO / MOF-808) in Example 1 and the original metal substrate film (Ti foam) in Comparative Example 1 under photoelectric conditions;

[0030] Figure 8 This is a graph showing the repeated degradation of 10 mg / L tetrabromophenol by the photoanode composite film (Ti foam / ZnO / MOF-808) in Example 1 under photoelectric conditions. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing an electric anode composite membrane, comprising the following steps:

[0032] The original metal substrate is sequentially placed in a ketone solvent, an alcohol solvent, and a mixed acid solution for ultrasonic immersion to perform degreasing and etching treatments, and then dried to obtain a pretreated metal substrate film;

[0033] The metal salt and the ligand powder are uniformly mixed with the mixed solution to obtain a precursor solution of the metal organic framework;

[0034] The precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the metal organic framework was obtained after cooling, washing and drying by a hydrothermal method;

[0035] A soluble zinc source is mixed with an alkaline solution, and zinc oxide particles with light-responsive characteristics are obtained by stirring, washing, and drying through a chemical precipitation method;

[0036] Dispersing zinc oxide particles and metal organic framework powder in a certain ratio in an alcohol solution and a dilute alcohol solution in turn by ultrasonication to obtain a composite photoelectrocatalyst dispersion;

[0037] The dispersion is slowly dripped onto the pretreated surface of the metal substrate, dried at room temperature and then calcined to obtain the photoanode composite film.

[0038] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.

[0039] The present invention provides a photoelectric catalyst, which is obtained by mixing a zirconium-based metal organic framework synthesized by a hydrothermal method and zinc oxide particles synthesized by a chemical precipitation method. In the present invention, the total loading amount of the composite photoelectric catalyst on the metal substrate is 2.672 to 4 mg / cm 2 , and more preferably 2.672 mg / cm 2. In the present invention, the preparation method of the zirconium-based metal organic framework preferably includes the following steps: mixing zirconium oxychloride octahydrate, trimesic acid, N,N-dimethylformamide and formic acid, stirring them thoroughly to obtain a precursor solution, and then transferring it to a stainless steel reactor lined with polytetrafluoroethylene, and obtaining the zirconium-based metal organic framework by a hydrothermal method. In the present invention, the metal salt is zirconium tetrachloride (ZrCl4) or zirconium oxychloride octahydrate (ZrOCl2·8H2O), and the metal ligand is one of terephthalic acid (H2BDC), trimesic acid (H3BTC), and porphyrin molecules, and is further preferably ZrOCl2·8H2O and H3BTC, and the molar ratio thereof is (1-4):1, and is further preferably 4:1; the mixed solution includes formic acid (HCOOH) and N,N-dimethylformamide (DMF), and the volume ratio thereof is (1-4):1, and is further preferably 1:1; the stirring time of the precursor solution is 15-6 0min, more preferably 20min; the hydrothermal temperature and time of the precursor solution are 100-140°C, 12-36h, more preferably 120°C, 24h; the cooling time after hydrothermal is 6-12h, more preferably 8h; the washing solution is acetone, methanol and pure water, and their volumes are 30-90mL, 60-120mL and 100-180mL, respectively, more preferably 30mL acetone, 90mL methanol and 150mL pure water; the drying temperature and time are 60-90°C, 8-16h, more preferably 60°C, 12h.

[0040] After obtaining the zirconium-based metal organic framework, another photoelectric catalyst zinc oxide of the present invention is synthesized by chemical precipitation method, wherein the soluble zinc source is zinc nitrate hexahydrate (Zn(NO3)2·6H2O) or zinc acetate dihydrate (Zn(CH3COO)2)·2H2O), and its concentration is 0.1-0.5 mol / L, and more preferably 0.3 mol / L zinc nitrate hexahydrate (Zn(NO3)2·6H2O); the alkaline solution is sodium hydroxide (NaOH) or potassium hydroxide (KOH), its concentration is 1-5 mol / L, more preferably 3 mol / L potassium hydroxide (KOH); the volume ratio of the reaction solution is 1:(1-3), more preferably 1:1; the stirring time is 15-45 min, more preferably 30 min; the washing solution is 100-200 mL of pure water, more preferably 150 mL of pure water; the drying temperature and time are 60-90°C, 8-16 h, respectively, more preferably 80°C, 12 h.

[0041] In the present invention, the composite photoelectric catalyst is a mixture of a zirconium-based metal organic framework obtained by a hydrothermal method and zinc oxide powder obtained by a chemical precipitation method. The present invention disperses the zirconium-based metal organic framework MOF-808 formed by octahydrate zirconium oxychloride and an organic ligand trimesic acid and zinc oxide powder formed by hexahydrate zinc nitrate and potassium hydroxide in ethanol to obtain a composite photoelectric catalyst dispersion. The mass ratio of the zinc oxide particles to the metal organic framework is (1-3):1, and more preferably 3:1; the alcohol solution is 100-500 μL ethanol, and more preferably 200 μL ethanol; the dilute alcohol solution includes ethanol and pure water, and the volume ratio is (1-5):1, and more preferably 3:1; the ultrasonic time is 15-45 min. The introduction of MOF materials, using the adjustability of its ligands, large specific surface area and high porosity, provides more active sites and additional migration pathways for the migration of photoinduced electrons in photocatalysis, thereby fundamentally promoting the separation of carriers and making up for the defects of rapid recombination of carriers in traditional photocatalysts.

[0042] After obtaining the composite electrocatalyst mixed solution, the composite photoelectric catalyst powder and its dispersion obtained by the present invention do not need to be subsequently modified, and the photoelectric anode composite film is obtained by loading the composite photoelectric catalyst onto the surface of the metal substrate by a drop coating method and then calcining. In the present invention, the metal substrate is one of titanium sheet, nickel foam, and porous titanium foam, and porous titanium foam is more preferably; the ketone solvent is acetone or butanone, and acetone is more preferably; the alcohol solvent is one of methanol and ethanol, and methanol is more preferably; the ultrasonic time is 5 to 30 minutes, and 15 minutes is more preferably; the mixed acid solution includes hydrofluoric acid (HF), nitric acid (HNO3) and water, and the volume ratio is 1: (1 to 5): (19 to 23), and 1: 3: 21 is more preferably; the immersion time is 30 to 90 seconds, and 60 seconds is more preferably; the drying temperature and time are 60 to 90 degrees Celsius, 8 to 16 hours, and 80 degrees Celsius, 12 hours.

[0043] In the present invention, the room temperature drying time of the metal substrate after drop coating of the dispersion is 30 to 90 minutes, more preferably 60 minutes; the calcination temperature and time are 300 to 450° C., 60 to 120 minutes, more preferably 400° C., 60 minutes.

[0044] The present invention provides a zirconium-based MOF composite film prepared by the preparation method described in the above technical solution, including a metal substrate and a functional photoelectric catalyst loaded on the surface of the metal substrate; the photoelectric catalyst is formed by mixing and dispersing a zirconium-based metal organic framework (MOF-808) and zinc oxide (ZnO) obtained by a chemical precipitation method. In the present invention, specifically, MOF-808 synthesized by a hydrothermal method using zirconium oxychloride octahydrate and an organic ligand trimesic acid and zinc oxide synthesized by a chemical precipitation method using zinc nitrate hexahydrate and potassium hydroxide are dispersed in an ethanol solution to obtain a composite photoelectric catalyst (ZnO / MOF-808). The ZnO / MOF-808 composite photoelectric catalyst provided by the present invention is stably loaded on the surface of the metal substrate, and there is no obvious detachment of the catalyst during multiple cycles of use.

[0045] The invention provides the application of the photoanode composite membrane described in the above scheme in the photoelectrocatalytic oxidation degradation of tetrabromophenol. In the present invention, the photoanode composite membrane can preferably be used as a photoanode filter membrane in the field of sewage treatment, which is convenient for recycling and reuse. It is more environmentally friendly, stable, efficient and energy-saving during use, and can achieve continuous operation, solving the problem that traditional granular powder catalysts are difficult to recycle and reuse after use.

[0046] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Example 1

[0048] A 2.5×2.5cm porous titanium foam was placed in 50mL acetone and 50mL methanol solution for ultrasonication for 15min in turn; after the ultrasonication, it was transferred to 25mL mixed acid solution (1mL hydrofluoric acid, 3mL nitric acid, 21mL pure water) and soaked for 1min, taken out, rinsed repeatedly with pure water, and vacuum dried at 80°C for 12h to obtain the pretreated original metal substrate (Ti foam).

[0049] 1.29 g zirconium oxychloride octahydrate and 0.21 g trimesic acid were added to a 60 mL mixture consisting of 30 mL N,N-dimethylformamide and 30 mL formic acid, and stirred at room temperature (25°C) for 20 min to obtain a clear and transparent MOF-808 precursor solution;

[0050] The MOF-808 precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in an oven at 120°C for 24 hours, and naturally cooled to room temperature for 8 hours after the reaction. The obtained white suspension was filtered through a vacuum filtration device and washed with 30 mL of acetone, 90 mL of methanol and 150 mL of pure water in sequence to wash away the excess acid and organic solvent during the reaction. The white powder was collected and vacuum dried at 60°C for 12 hours to obtain a zirconium-based metal organic framework, recorded as MOF-808;

[0051] 50 mL of 0.3 mol / L zinc nitrate hexahydrate solution and 50 mL of 3 mol / L potassium hydroxide solution were mixed, stirred at room temperature for 30 min, washed with 150 mL of pure water by vacuum filtration until neutral, and then white powder was collected and dried at 80 °C in vacuum for 12 h to obtain zinc oxide particles, recorded as ZnO;

[0052] 12.5 mg ZnO powder and 4.2 mg MOF-808 powder were dispersed in 200 μL ethanol solution, and after ultrasonication for 30 min, 60 μL was added and ultrasonication was continued for 30 min to obtain a composite photoelectrocatalyst dispersion;

[0053] The dispersed liquid was dropwise coated on the pretreated porous titanium foam surface, dried at room temperature for 60 minutes, and then heated in a tubular furnace at 350° C. for 60 minutes to load the composite photoelectrocatalyst on the porous titanium foam surface to obtain a photoanode composite film (Tifoam / ZnO / MOF-808).

[0054] Comparative Example 1

[0055] The Ti foam catalytic membrane was prepared according to the method of Example 1, except that the subsequent step of adding the composite photoelectric catalyst was omitted.

[0056] A 2.5×2.5cm porous titanium foam was placed in 50mL acetone and 50mL methanol solution for ultrasonication for 15min in turn; after the ultrasonication, it was transferred to 25mL mixed acid solution (1mL hydrofluoric acid, 3mL nitric acid, 21mL pure water) and soaked for 1min, taken out, rinsed repeatedly with pure water, and vacuum dried at 80°C for 12h to obtain the pretreated original metal substrate (Ti foam).

[0057] Figure 1 This is a scanning electron microscope image of MOF-808. Figure 1 It can be seen that the MOF-808 particles are in the shape of regular octahedral cubes, which is one of the typical shapes of MOF-808, thus proving that MOF-808 was successfully prepared.

[0058] Figure 2 This is the scanning electron microscope image of ZnO. Figure 2It can be seen that ZnO exhibits a flower-like structure composed of “micro-petals”, which has been reported in the literature, proving that the material preparation was successful.

[0059] Figure 3 This is a scanning electron microscope image of the photoanode composite film (Ti foam / ZnO / MOF-808). Figure 3 It can be seen that there is a cubic loading on the petal-shaped ZnO surface, proving that the composite photoelectrocatalyst is successfully composited and loaded on the Ti foam surface.

[0060] Figure 4 The linear voltammetry (LSV) curves of Ti foam / ZnO / MOF-808 and the original metal substrate (Ti foam) are shown in Figure 2. Figure 4 It can be seen that after the composite photoelectric catalyst is loaded on the Ti foam surface, the oxygen evolution potential is significantly improved, thereby reducing the occurrence of side reactions in the electrocatalytic reaction.

[0061] The performance tests of the membrane materials prepared in Example 1 and Comparative Example 1 are as follows:

[0062] (1) Ti foam / ZnO / MOF-808 catalytic degradation of tetrabromophenol

[0063] Prepare 50mL of tetrabromophenol solution with a concentration of 10mg / L, and use a sodium sulfate solution with a concentration of 50mM / L as the supporting electrolyte. Use the Ti foam / ZnO / MOF-808 photoelectric membrane in Example 1 as the anode. In the circulating filtration system, the cathode is at the top of the system and the vertical distance between the cathode and the anode is 3mm. Select the Ti mesh as the cathode. In the circulating filtration system, a peristaltic pump is used to provide a flow rate of 1mL / min to circulate the solution in the system. Under the conditions of no light and no electricity, pure electricity and photoelectricity, tetrabromophenol is degraded by circulating filtration in the device for 60min, and repeated experiments are carried out under photoelectric conditions to verify the repeatability of Ti foam / ZnO / MOF-808. The electrocatalytic experiment uses a DC power supply at 7mA / cm 2 An external electric field was provided at a constant current density of , and light was provided by a 200 W xenon lamp in the photoelectrocatalytic experiment. During the degradation process, samples were taken at different times for concentration analysis. The degradation efficiency of tetrabromophenol by the photoanode composite film of Example 1 under different reaction conditions and the repeatability under photoelectric conditions were calculated based on the concentration changes.

[0064] (2) Ti foam catalytic degradation of tetrabromophenol experiment

[0065] 50mL of tetrabromophenol solution with a concentration of 10mg / L was prepared, and a sodium sulfate solution with a concentration of 50mM / L was used as the supporting electrolyte. The Ti foam catalytic membrane in Comparative Example 1 was used as the anode. In the circulating filtration system, the cathode was at the top of the system and the vertical distance between the cathode and the anode was 3mm. The Ti mesh was selected as the cathode. In the circulating filtration system, a peristaltic pump was used to provide a flow rate of 1mL / min to circulate the solution in the system. Under the conditions of no light and no electricity, pure electricity and photoelectricity, tetrabromophenol was degraded by circulating filtration in the device for 60min. The electrocatalytic experiment used a DC power supply at 7mA / cm 2 An external electric field was provided at a constant current density of , and light was provided by a 200W xenon lamp in the photoelectrocatalytic experiment. During the degradation process, samples were taken at different times for concentration analysis, and the degradation efficiency of tetrabromophenol by the Ti foam catalytic membrane in Comparative Example 1 under different reaction conditions was calculated based on the concentration changes.

[0066] Figure 5 The degradation comparison of 10 mg / L tetrabromophenol by the photoanode composite film (Ti foam / ZnO / MOF-808) in Example 1 under no light and no electricity, pure electricity and photoelectric conditions is shown in Figure 1. Figure 5 It can be seen that the Ti foam / ZnO / MOF-808 film has no obvious degradation of tetrabromophenol under no light and no electricity conditions; it has a certain degradation effect on tetrabromophenol under pure electricity conditions, and the degradation effect of tetrabromophenol under photoelectric conditions is significantly improved.

[0067] Figure 6 The degradation comparison of the original metal substrate film (Ti foam) in Comparative Example 1 to 10 mg / L tetrabromophenol under no light and no electricity, pure electricity and photoelectric conditions is shown in Figure 1. Figure 6 It can be seen that the Ti foam catalytic membrane has no obvious degradation of tetrabromophenol under no light and no electricity conditions; it has a certain degradation effect on tetrabromophenol under pure electricity conditions, while the degradation effect on tetrabromophenol under photoelectric conditions is not significantly different from that under pure electricity conditions.

[0068] Figure 7 The degradation comparison diagram of 10 mg / L tetrabromophenol by the photoanode composite film (Ti foam / ZnO / MOF-808) in Example 1 and the original metal substrate film (Ti foam) in Comparative Example 1 under photoelectric conditions; Figure 7 It can be seen that the degradation efficiency of tetrabromophenol by the Ti foam / ZnO / MOF-808 composite membrane under photoelectric conditions is significantly higher than that of the Ti foam catalytic membrane, which proves that the photoanode composite membrane of the present invention has a significant effect under photoelectric conditions.

[0069] Figure 8This is a graph showing the repeated degradation of 10 mg / L tetrabromophenol by the photoanode composite film (Ti foam / ZnO / MOF-808) in Example 1 under photoelectric conditions. Figure 8 It can be seen that the degradation efficiency of the Ti foam / ZnO / MOF-808 composite film did not decrease significantly after repeating the experiment 5 times under photoelectric conditions.

[0070] In summary, the test examples prove that the photoelectric anode composite membrane (Ti foam / ZnO / MOF-808) provided by the present invention has a good degradation effect on organic pollutants in wastewater under photoelectric conditions; the preparation method of the photoelectric anode composite membrane provided by the present invention is simple, convenient for catalyst recovery, and the degradation efficiency does not decrease significantly after repeated use.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A zirconium-based MOF composite film for photoelectric degradation, characterized in that: The invention comprises a metal substrate and a composite photoelectric catalyst which are stacked in sequence. The composite photoelectric catalyst is a sheet-like zinc oxide particle and a zirconium-based metal organic framework with an octahedral cubic morphology.

2. The zirconium-based MOF composite membrane according to claim 1, characterized in that: The total loading amount of the composite photoelectric catalyst on the metal substrate is 2.672-4 mg / cm 2 .

3. A method for preparing a zirconium-based MOF composite membrane according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: The original metal substrate is sequentially placed in a ketone solvent, an alcohol solvent, and a mixed acid solution for ultrasonic immersion to perform degreasing and etching treatments, and then dried to obtain a pretreated metal substrate film; The metal salt and the ligand powder are uniformly mixed with the mixed solution to obtain a precursor solution of the metal organic framework; The precursor solution was transferred to a stainless steel reactor lined with polytetrafluoroethylene, and the metal organic framework was obtained after cooling, washing and drying by a hydrothermal method; A soluble zinc source is mixed with an alkaline solution, and zinc oxide particles with light-responsive characteristics are obtained by stirring, washing, and drying through a chemical precipitation method; Dispersing zinc oxide particles and metal organic framework powder in a certain ratio in an alcohol solution and a dilute alcohol solution in turn by ultrasonication to obtain a composite photoelectrocatalyst dispersion; The dispersion is slowly dripped onto the pretreated surface of the metal substrate, dried at room temperature and then calcined to obtain the photoanode composite film.

4. The preparation method according to claim 3, characterized in that: The metal substrate is one of titanium sheet, nickel foam, and porous titanium foam; the ketone solvent is acetone or butanone; the alcohol solvent is one of methanol and ethanol; the ultrasonic time is 5 to 30 minutes; the mixed acid solution includes hydrofluoric acid, nitric acid and water, and the volume ratio thereof is 1:(1 to 5):(19 to 23); the immersion time is 30 to 90 seconds; the drying temperature and time are 60 to 90°C and 8 to 16 hours respectively.

5. The preparation method according to claim 3, characterized in that: The molar ratio of the metal salt to the ligand powder is (1-4):1, and the mixed solution includes formamide and N,N-dimethylformamide in a volume ratio of (1-4):

1.

6. The preparation method according to claim 3, characterized in that: The stirring time of the precursor solution is 15 to 60 minutes; the hydrothermal temperature and time of the precursor solution are 100 to 140° C. and 12 to 36 hours respectively; the cooling time after hydrothermal is 6 to 12 hours; The washing solution is acetone, methanol and pure water, and the volumes thereof are 30-90 mL, 60-120 mL and 100-180 mL respectively; The drying temperature and time are 60-90° C. and 8-16 hours respectively.

7. The preparation method according to claim 3, characterized in that: The soluble zinc source is hexahydrate nitric acid or dihydrate acetic acid, and its concentration is 0.1-0.5 mol / L; the alkaline solution is sodium hydroxide or potassium hydroxide, and its concentration is 1-5 mol / L; the volume ratio of the reaction solution is 1:(1-3); the stirring time is 15-45 min; the washing solution is 100-200 mL pure water; the drying temperature and time are 60-90° C. and 8-16 h, respectively.

8. The preparation method according to claim 3, characterized in that: The mass ratio of the zinc oxide particles to the metal organic framework is (1-3):1; the alcohol solution is 100-500 μL of ethanol; the dilute alcohol solution includes ethanol and pure water in a volume ratio of (1-5):1; and the ultrasonic time is 15-45 min.

9. The preparation method according to claim 3, characterized in that: The room temperature drying time of the metal substrate after the dispersion is dripped is 30 to 90 minutes; the calcination temperature and time are 300 to 450° C. and 60 to 120 minutes respectively.

10. An application of the zirconium-based MOF composite membrane according to claim 1 or 2 in a circulating filtration system for removing organic pollutants in wastewater, characterized in that: The organic pollutant is tetrabromophenol; the pollutant-containing influent water includes a sodium sulfate electrolyte with a concentration of 50 mM.